Cultural Visibility and Urban Justice in immigrant neighbourhoods of Amsterdam - Sezer, Ceren; Fernandez Maldonado, Ana Maria (A+BE | Architecture and the Built Environment, 2020)
This study investigates transformation processes in the streets of immigrant neighbourhoods in Amsterdam. It approaches the issue through the visibility of immigrant amenities – such as shops, restaurants, places of worship – with distinctive cultural signs and practices, that are recognizable in public spaces. The study analyses cultural visibility on two streets with a concentration of immigrant amenities, in 2007 and 2016. It approaches cultural visibility from two aspects: the physical setting and the people’s activities in these streets. The findings reveal that the different architectural types and location of the neighbourhoods, and their different processes of urban renewal, have produced different outcomes in terms of cultural visibility.